2019
DOI: 10.1016/s2468-2667(19)30108-2
|View full text |Cite
|
Sign up to set email alerts
|

20-year trends in cause-specific heart failure outcomes by sex, socioeconomic status, and place of diagnosis: a population-based study

Abstract: Summary Background Heart failure is an important public health issue affecting about 1 million people in the UK, but contemporary trends in cause-specific outcomes among different population groups are unknown. Methods In this retrospective, population-based study, we used the UK Clinical Practice Research Datalink and Hospital Episodes Statistics databases to identify a cohort of patients who had a diagnosis of incident heart failure between Jan 1, 1998, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
5
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 32 publications
(60 reference statements)
5
83
5
7
Order By: Relevance
“…It has been estimated that 1‐year costs related to HF in the European Union are around €29 billion, 9 with frequent, prolonged and repeat hospitalizations accounting for the majority of these costs 10 . The economic burden of HF is likely to increase substantially over the next decade, driven by the ageing of the population and an estimated 46% increase in HF prevalence by 2030 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 1‐year costs related to HF in the European Union are around €29 billion, 9 with frequent, prolonged and repeat hospitalizations accounting for the majority of these costs 10 . The economic burden of HF is likely to increase substantially over the next decade, driven by the ageing of the population and an estimated 46% increase in HF prevalence by 2030 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…Inequity in HF care place socially deprived patients with HFrEF at double risk. Low socioeconomic status is a substantial risk factor of developing HF, 6 and recent studies indicate that income, poverty, and employment status is associated with a poor clinical outcome, for example, mortality and readmission among patients after being diagnosed with HF in universal healthcare systems 7–10,27 . Some studies have shown a relationship between HF care processes delivered (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Low socioeconomic status is a strong predictor for the development of HF 6 . In addition, differences in readmission risk and mortality according to a level of income and socioeconomic deprivation have been reported in several studies among patients with HF, even in tax‐financed well‐fare state settings, 7–11 while socioeconomic deprivation, defined with the Index of Multiple Deprivation 2007, have not been found to be associated with mortality in one study 12 . Socioeconomic disparities in HF care may potentially contribute to the observed differences in mortality and readmission risk according to socioeconomic status.…”
Section: Introductionmentioning
confidence: 91%
“…However, as the impact of this chronic condition increases on health services, the nature of living with, rather than dying from, heart failure is of increasing importance to patients and health services alike. Claire Lawson and colleagues' 4 Article in The Lancet Public Health provides one of the first studies of its scale to examine trends in secondary outcomes of heart failure and corresponding socioeconomic inequalities.…”
mentioning
confidence: 99%
“…This previous work identified increases in age and multimorbidity at diagnosis of heart failure. Lawson and colleagues' study 4 builds on this previous work to characterise the patient journey and their outcomes from heart failure diagnosis onwards. By identifying incident cases in primary care and following them up, rather than relying on hospital diagnoses alone, this study provides a comprehensive overview on morbidity and cause-specific health service use through to ultimate cause of death.…”
mentioning
confidence: 99%